PROPOSTA DE PLANO DE OBRA INTEGRANDO QUALIDADE, MEIO AMBIENTE E SEGURANÇA APLICADO À INDÚSTRIA DA CONSTRUÇÃO CIVIL: Contribuição para a construção sustentável - Pereira, Rodrigo (2003)
This present study aims to contribute to the development of a recommendation list for implementing a management-integrated system in the civil construction industry. The view towards an integrated management system taking into account quality, environment and (Working) safety is a future strategy where industrial organizations will have to adequate themselves in order to become more competitive and developed. The construction quality plan will be made use of it, as the main point to fease the implementation of the aims in the civil construction industry. As a case study that will be developed in an expanding commercial undertaking in the city of Niterói, Rio de Janeiro, Brazil.